The Effect of Effleurage Massage on Reducing Labor Pain in Laboring Mothers at Puskesmas Sarimotandang Sidamanik Year 2022 - Fithri, Nurhamida (International Archives of Medical Sciences and Public Health, 2024)
Background; Massage or massage on the abdomen (effleurage) is a form of skin stimulation used during labor in reducing pain effectively. This study aims to determine the effect of Massage Effleurage on Reducing Labor Pain in Maternity. Method; This research is an analytical research with experimental study design with one group pre and postest design. The population in this study were all laboring mothers at Sarimotandang Health Center as many as 35 people. Data collection was done by distributing questionnaires to respondents. Data processing starts from editing, coding, entry, cleaning and tabulating data. Data analysis using paired T test. Results; The results showed that there was an effect of labor pain in laboring mothers before and after being given effleurage massage (p = 0.000). Conclusion; Thus it is recommended to the mother of the baby to do counseling to health workers related to the problem of labor pain.